2022
DOI: 10.2147/ijgm.s355913
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obstetric Factors on the Occurrence of Pelvic Floor Dysfunction in Women in the Early Postpartum Period

Abstract: Background This study aimed to analyze the effect of obstetric factors on the development of pelvic floor dysfunction (PFD) in women in the early postpartum period. Methods Clinical data of 300 women who were reviewed in our outpatient clinic from July 2016 to December 2019 in the postpartum period were retrospectively analyzed. The occurrence of pelvic organ prolapse (POP) and stress urinary incontinence (SUI) was assessed using the Pelvic Organ Prolapse Quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The effect of weight factors on pelvic floor function has been a hot topic. Most studies have focused on the effects of maternal prepregnancy body mass index (BMI) and newborn birthweight on pelvic floor function [9][10][11], and few studies have explored the effects of GWG as a controllable factor during pregnancy on pelvic floor function. A systematic review and meta-analysis showed that excessive GWG is one of the risk factors for PFDs [12], and this limited study did not address the twin primiparas group.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of weight factors on pelvic floor function has been a hot topic. Most studies have focused on the effects of maternal prepregnancy body mass index (BMI) and newborn birthweight on pelvic floor function [9][10][11], and few studies have explored the effects of GWG as a controllable factor during pregnancy on pelvic floor function. A systematic review and meta-analysis showed that excessive GWG is one of the risk factors for PFDs [12], and this limited study did not address the twin primiparas group.…”
Section: Introductionmentioning
confidence: 99%
“…Constipation, stimulants like coffee, obesity, hypertension, sedatives, or anti-inflammatory drugs may be associated with the onset or worsening of pelvic floor dysfunction symptoms [ 12 ]. Concerning the obstetrics background, a long labor stage of delivery, vaginal delivery, pelvic floor tears or incontinence during pregnancy are risk factors for pelvic floor dysfunctions subsequently [ 13 ]. High-impact sports have also been described as another risk factor for pelvic floor disorders [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of weight factors on pelvic oor function has been a hot topic. Most studies have focused on the effects of maternal prepregnancy BMI and newborn birthweight on pelvic oor function [9][10][11], and few studies have explored the effects of GWG as a controllable factor during pregnancy on pelvic oor function. A systematic review and meta-analysis showed that excessive GWG is one of the risk factors for PFDs [12], and this limited study did not address the twin primiparas group.…”
mentioning
confidence: 99%